Analisis Semiotika Pada Teks Al-Qur’an Tentang “Khamar” Dalam Pendekatan Semanalisis Hingga Intertekstualitas Julia Kristeva - Muhammad Sakti Garwan (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
Community problems that are increasing day by day, both in social conditions between people in real terms up to social media is a matter that must be seen in a good scientific perspective, so that the problem can be resolved properly according to the right position. This is what makes the importance of the role of science and religion in seeing this, especially in the matter of liquor or khamar, which is viewed in the perspective of science about literature or language, namely the science of semiotics that has developed since ancient Greece. This proves that, language is a very important thing for life, namely as a tool to communicate and serves as a tool to test existing arguments. In this study, the author tries to examine how the role of linguistics, or semiotics from a figure named Julia Kristeva, with a semanalysis approach to intertextuality, in answering the social problem of the law of liquor or khamar, which is referred to by the Qur'an.